2012
DOI: 10.1080/19475411.2011.650233
|View full text |Cite
|
Sign up to set email alerts
|

An artificial lateral line system using IPMC sensor arrays

Abstract: Most fish and aquatic amphibians use the lateral line system, consisting of arrays of hair-like neuromasts, as an important sensory organ for prey/predator detection, communication, and navigation. In this paper a novel bio-inspired artificial lateral line system is proposed for underwater robots and vehicles by exploiting the inherent sensing capability of ionic polymer-metal composites (IPMCs). Analogous to its biological counterpart, the IPMC-based lateral line processes the sensor signals through a neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 42 publications
0
84
0
Order By: Relevance
“…A novel bio-inspired artificial lateral line system is achieved by exploiting the inherent sensing capability of ionic polymer-metal composites (IPMCs) (Abdulsadda et al 2011(Abdulsadda et al , 2012 which is shown in Fig. 14b.…”
Section: Piezoelectric and Magnetic Allfsmentioning
confidence: 99%
“…A novel bio-inspired artificial lateral line system is achieved by exploiting the inherent sensing capability of ionic polymer-metal composites (IPMCs) (Abdulsadda et al 2011(Abdulsadda et al , 2012 which is shown in Fig. 14b.…”
Section: Piezoelectric and Magnetic Allfsmentioning
confidence: 99%
“…[57][58][59][60] Recent applications of IPMC sensing capabilities span the measurement of force, flow, shear loading, curvature, structural health monitoring and energy harvesting. [61][62][63][64][65][66][67][68][69] IPMCs generate charges when experiencing a mechanical load or deformation. If the polymer is not deformed, the distribution of cations inside the polymer is uniform and no output voltage is detected.…”
Section: -19mentioning
confidence: 99%
“…With the exception of the hot-wire array presented by Yang et al [28], biomimetic approaches picked up fluid motion by means of a flow-induced deflection of a cantilever-like or lamella-shaped structure (an artificial cupula), which was detected by piezo-electric [38], resistive [39][40][41][42][43], capacitive [44][45][46], ionic polymer-metal composite (IPMC)-based [29,47] or optical [48][49][50][51] read-out techniques.…”
Section: Biomimetic Flow Sensors: State Of the Artmentioning
confidence: 99%
“…The capacitive detection principle was also used to fabricate bioinspired sensors based on fish SNs that contained an SU-8 hair cell [46,62]. Some flow sensors are based on the piezo-electric or depolarization detection principle [47,[63][64][65][66]. These hair cell-inspired sensors were made from ionic polymer-metal composites (IPMCs).…”
Section: Biomimetic Flow Sensors: State Of the Artmentioning
confidence: 99%